Study of psychological state of cancer patients undergoing radiation therapy during novel coronavirus outbreak and effects of nursing intervention. Issue 2 (26th November 2020) - Lou, Shuchang; Xu, Dejing; Li, Xiaodong; Huan, Yan; Li, Jun
Abstract: Objective: To investigate psychological state of hospitalized cancer patients undergoing radiation therapy and evaluate effects of customized psychological intervention on patients' psychological state during novel Coronavirus (COVID‐19) outbreak. Method: Fifty‐eight hospitalized head and neck cancer patients undergoing radiation therapy were included and received online and offline psychological intervention. General information questionnaire and the Self‐Report Symptom Inventory, Symptom Check‐List90 (SCL‐90) were utilized to investigate and analyze psychological state of hospitalized head and neck cancer patients undergoing radiation therapy before and after intervention. Self‐Rating Depression Scale (SDS) and Self‐Rating Anxiety Scale (SAS) were used to evaluate depression severity and anxiety severity of them. Results: Overall psychological state of patients (include nine symptom dimensions: somatization, obsessive, interpersonal sensitivity, depression, anxiety, hostility, phobic anxiety, paranoid ideation, and psychoticism) was improved significantly after intervention ( P  < .05). Moreover, scores of SAS and SDS were lowered. Conclusion: Customized psychological intervention helped to improve overall psychological state of hospitalized cancer patients undergoing radiation therapy during COVID‐19 outbreak and showed encouraging effects on reduction severity of depression and anxiety.